Aligning Software Product Management with Software Engineering Concepts: A Systematic Literature Review - Oruthotaarachchi, Chalani; Wijayanayake, Janaka (Universitas Airlangga, 2025)
Background: Software Product Management (SPM) plays a vital role in the success of many software projects by aligning customer needs with their business objectives and ensuring a seamless and effective software product lifecycle. SPM is established as a collection of tools, techniques, and practices that help an organization accomplish its objectives and enhance the predictability and profitability of software product development. However, despite its significance, SPM research has been fragmented into specific topics having limited SPM literature reviews. This research study addresses this gap and discusses the status of the SPM domain in a more holistic spectrum. Objective: The study aims to review recent literature on SPM, focusing on the alignment of SPM with software engineering concepts, a product manager’s role, the existing framework, ontologies, and best practices that support ensuring the success of a product manager’s role. Methods: A systematic literature review was conducted using SCOPUS, IEEE Xplore, ACM Digital Library, ScienceDirect, and ProQuest Central as databases. 71 articles were selected following a rigorous screening process as per the PRISMA 2000 statement. Results: Integrating SPM and SE is crucial in delivering value-driven software solutions. Available theoretical models and frameworks can help with this integration; however, implementing these frameworks often has challenges. Even though product managers play a vital role in the software lifecycle, they lack sufficient organizational support to enrich their skills and knowledge. Other major challenges are the lack of knowledge to use emerging technologies such as AI for data-driven decision-making processes and the tendency to replace humans with such technologies. Conclusion: Aligning strategic vision with agile flexibility is important to integrate SPM with SE practices. To improve decision-making and ensure better alignment of SPM with business objectives, organizations have to enhance product managers’ capabilities by leveraging emerging technologies. Research can focus on developing adaptable and user-friendly SPM frameworks that match both medium-scale and large-scale organizational expectations. Keywords: Organizational Value, Product Manager Role, Software Engineering Integration, Software Product Management, SPM Challenges, SPM Frameworks